2014
DOI: 10.1111/maps.12389
|View full text |Cite
|
Sign up to set email alerts
|

NanoSIMS analysis of organic carbon from the Tissint Martian meteorite: Evidence for the past existence of subsurface organic‐bearing fluids on Mars

Abstract: Two petrographic settings of carbonaceous components, mainly filling open fractures and occasionally enclosed in shock‐melt veins, were found in the recently fallen Tissint Martian meteorite. The presence in shock‐melt veins and the deuterium enrichments (δD up to +1183‰) of these components clearly indicate a pristine Martian origin. The carbonaceous components are kerogen‐like, based on micro‐Raman spectra and multielemental ratios, and were probably deposited from fluids in shock‐induced fractures in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 57 publications
2
33
0
3
Order By: Relevance
“…analyses of the Tissint meteorite reported by several groups on separate meteorite portions have shown varying results. However, analysis of several other impact melt pockets within Tissint failed to show these features(Barrat et al, 2014;Peters et al, 2015), and still other analyses reported variable abundances within a single sample and even within a single impact vein(Chen et al, 2015;Walton et al, 2014).Several hypotheses have been proposed to explain this heterogeneity in Tissint: (1) regolith-derived components introduced in the absence of fluids(Gattacceca et al, 2013), (2) terrestrial contamination from the interaction of desert sand and dew during Tissint's brief residence in the hot desert environment(Barrat et al, 2014), and (3) fluid inclusions resulting in oxidation and precipitation of soluble material(Aoudjehane et al, 2012;Chen et al, 2015;Lin et al, 2014;Steele et al, 2018). However, analysis of several other impact melt pockets within Tissint failed to show these features(Barrat et al, 2014;Peters et al, 2015), and still other analyses reported variable abundances within a single sample and even within a single impact vein(Chen et al, 2015;Walton et al, 2014).Several hypotheses have been proposed to explain this heterogeneity in Tissint: (1) regolith-derived components introduced in the absence of fluids(Gattacceca et al, 2013), (2) terrestrial contamination from the interaction of desert sand and dew during Tissint's brief residence in the hot desert environment(Barrat et al, 2014), and (3) fluid inclusions resulting in oxidation and precipitation of soluble material(Aoudjehane et al, 2012;Chen et al, 2015;Lin et al, 2014;Steele et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…analyses of the Tissint meteorite reported by several groups on separate meteorite portions have shown varying results. However, analysis of several other impact melt pockets within Tissint failed to show these features(Barrat et al, 2014;Peters et al, 2015), and still other analyses reported variable abundances within a single sample and even within a single impact vein(Chen et al, 2015;Walton et al, 2014).Several hypotheses have been proposed to explain this heterogeneity in Tissint: (1) regolith-derived components introduced in the absence of fluids(Gattacceca et al, 2013), (2) terrestrial contamination from the interaction of desert sand and dew during Tissint's brief residence in the hot desert environment(Barrat et al, 2014), and (3) fluid inclusions resulting in oxidation and precipitation of soluble material(Aoudjehane et al, 2012;Chen et al, 2015;Lin et al, 2014;Steele et al, 2018). However, analysis of several other impact melt pockets within Tissint failed to show these features(Barrat et al, 2014;Peters et al, 2015), and still other analyses reported variable abundances within a single sample and even within a single impact vein(Chen et al, 2015;Walton et al, 2014).Several hypotheses have been proposed to explain this heterogeneity in Tissint: (1) regolith-derived components introduced in the absence of fluids(Gattacceca et al, 2013), (2) terrestrial contamination from the interaction of desert sand and dew during Tissint's brief residence in the hot desert environment(Barrat et al, 2014), and (3) fluid inclusions resulting in oxidation and precipitation of soluble material(Aoudjehane et al, 2012;Chen et al, 2015;Lin et al, 2014;Steele et al, 2018).…”
mentioning
confidence: 99%
“…Some have reported a light rare earth element enrichment, high sulfur concentrations, and abundant volatiles within impact melt veins compared to the whole rock(Aoudjehane et al, 2012;Brennecka et al, 2014;Gattacceca et al, 2013;Lin et al, 2014;Walton et al, 2014). Some have reported a light rare earth element enrichment, high sulfur concentrations, and abundant volatiles within impact melt veins compared to the whole rock(Aoudjehane et al, 2012;Brennecka et al, 2014;Gattacceca et al, 2013;Lin et al, 2014;Walton et al, 2014).…”
mentioning
confidence: 99%
“…The amorphous nature of the organics (Figure ) indicates that Y000593 has not experienced high pressures and temperatures that would produce crystalline graphitic carbon or diamonds, expected from intense impact‐induced shock metamorphism (Garvie & Busek, ; Steele et al, ). Nor is the Y000593 organic carbon hosted by shock‐melt veins, as seen in recent studies of the martian meteorite Tissint, for example (Lin et al, ). In addition, we exclude electrochemical reduction as a source for the organic carbon as recently proposed by Steele et al (), for some of the reduced carbon found in the meteorites Tissint, Nakhla, and NWA 1950 where the carbon is intimately linked to titano‐magnetite, sulfides, and their alteration products, which differs from the close association with iddingsite and olivine that we see in Y000593.…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous organic carbon has been found in several martian meteorites and a variety of sources have been proposed, including: (i) high‐pressure impact generation (Steele et al, ); (ii) primary igneous, that is, magmatic processes (e.g., Steele, McCubbin, Fries, Golden et al, Steele, McCubbin, Fries, Kater 2012); (iii) electrochemical reduction (e.g., Steele et al, ); (iv) dead martian organisms (McKay et al, ); (v) reactions in rapidly cooling magmatic and, or impact‐generated gases (Zolotov & Shock, ); (vi) subsurface hydrothermal fluids (Lin et al, ; Steele et al, ); and (vii) exogenous delivery to Mars (e.g., Sephton et al, ). On the basis of the distribution and ultrastructure of the organics in Y00593 (see discussion of the TEM‐EELS data in the previous section), we have excluded the first three potential sources.…”
Section: Discussionmentioning
confidence: 99%
“…The carbon isotopic composition of these components provides “a tantalizing hint” for their biogenic origin on Mars (Lin et al. ), although it is possible that these are just terrestrial contaminations.…”
Section: Introductionmentioning
confidence: 99%